Prevención del consumo de alcohol en los adolescentes de la Comunidad Puerramal - Muepaz Escobar, Dayana Lisseth (2024)
Over the last years, alcoholism has been considered a public health problem, therefore this research was entitled: Prevention of alcohol consumption in teenagers of the Puerramal community, and its objective was to implement prevention strategies of alcohol consumption in teenagers of the Puerramal community. The research was developed under the quantitative modality, using quantitative paradigms, the cross sectional research was applied, descriptive, field and bibliographic, using the methods such as inductive- deductive, analytic -synthetic, historic-logic and systemic approach. The sample of the research was made up to 60 teenagers, to whom it was applied the Audit test, composed by 10 questions for gathering the information, allowing in this way, to obtain the following relevant results: 98%of the teenagers presented a probable addiction to alcohol, and 2% of the population presented a high risk. It is essential to consider these results as the focus of this research, given that they allowed to create a proposal based on educational intervention strategies based on the functions of the population under this research, such as: education, promotion and prevention, in which several educational, recreational activities along with educational techniques were carried out, leading to develop efficiently the proposal with the support of the community, and finally evidencing the results mentioned previously